THE ROLES BUDI UTOMO IN WOMEN’S ORGANIZATION MOVEMENTS IN 1928-1940 - Brigida, Intan Printina (International Journal of Humanity Studies (IJHS), 2019)
This article is the result of research on the role of Budi Utomo as the driving force of women’s movement. The article attempts to describe the track records of women and their organizations during 1928-1940 which were inspired by Budi Utomo youth movement as a reformation movement of Indonesian people. The type of research is a historical research, i.e. the description of the roles of Budi Utomo as a motor of women’s movements during 1928-1940. The method employed in the research is a library study using historical analysis. The findings revealed the development of Budi Utomo movement and its roles in mobilizing women during 1928-1940.DOI: 10.24071/ijhs.2019.020210